A Novel Bromodomain Inhibitor Reverses HIV-1 Latency through Specific Binding with BRD4 to Promote Tat and P-TEFb Association - Huang, Huachao; Liu, Shuai; Jean, Maxime; Simpson, Sydney; Huang, He; Merkley, Mark; Hayashi, Tsuyoshi; Kong, Weili; Rodríguez-Sánchez, Irene; Zhang, Xiaofeng; Yosief, Hailemichael O.; Miao, Hongyu; et al. (Frontiers in Microbiology, 2017)
Although combinatory antiretroviral therapy (cART) is effective to reduce HIV-1 viremia, it does not eliminate HIV-1 infection. HIV-1 remains latent with the presence of cART, impeding the cure of HIV-1/AIDS. Recently, latency-reversing agents (LRAs) have been developed to purge latent HIV-1, providing an intriguing strategy for eradication of residual, latent viral reservoirs. Our earlier studies show that the first-generation, methyl-triazolo bromodomain and extra-terminal domain inhibitor (BETi), JQ1, facilitates the reversal of HIV-1 latency. BETis have recently emerged as a new class of compounds that are promising for HIV-1 “shock and kill” eradication approach. However, due to the stochastic effcts of HIV-1 reactivation (Ho et al, Cell, 2013), JQ1 only modestly reverses HIV-1 latency as a single drug, which complicates the study of the underlining mechanisms. Thus, BETis, which are more potent, easier for synthesis, and with more structural diversity, are currently under active development. One such compound is UMB-32, a novel second-generation, 3,5-dimethylisoxazole BETi based on an imidazo[1,2-a]pyrazine scaffold. We screened 37 UMB-32 derivatives and identified that UMB-136 consistently reactivates HIV-1 in multiple cell models of HIV-1 latency with better efficiency than JQ1 and UMB-32. UMB-136 enhances HIV-1 Tat-LTR mediated transcription and increases HIV-1 viral production. Furthermore, UMB-136 enhances the latency-reversing effect of PKC agonists (prostratin, bryostatin-1) in CD8-depleted PBMCs containing HIV-1 latent reservoirs. Thus, our results illustrate that structurally improved BETis, such as UMB-136, would be useful as promising LRAs for HIV-1 eradication.